A Survey on Awareness, Knowledge, and Attitudes toward Epilepsy in an Urban Community in Turkey - Macit, C.; Clark, P. M.; Taner, N.; Bingol, C.; Mercanoglu, G.; Yuksel, G. (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2018)
Background and Aim: Epilepsy is one of the most common chronic neurological disorders with a high prevalence. Epileptic people and their family members suffer more from social stigma than the disorder itself. Among various complex reasons knowledge and awareness about epilepsy are the two important factors underlying discriminatory attitudes towards epileptic people. Community pharmacists play a major role in the care of these patients. In this study we mainly aimed to gain insights into the knowledge and awareness of and attitudes (AKA) towards epilepsy both in epileptic and healthy individuals in an urban community. To this end we also aimed at developing a reliable and valid measurement tool to assess AKA levels. Materials and Methods: This study was conducted in 13 community pharmacies with 219 respondents. Factor analysis yielded three clear subscales. Results: It was found that a vast majority of the participants were familiar with epilepsy; yet only 18 of them had detailed information. The community pharmacists were indicated as a main source of information about epilepsy at the same rate to that of physicians. Although most of the respondents knew that epilepsy was not a form of mental illness only about one forth of them knew the real cause. More than half of the respondents supported the epileptics' socialization in the community. Conclusion: We believe that the questionnaire developed in the study is a promising instrument for determining educational needs and offering guidance to healthcare professionals in developing standardized educational tools and programs.
Keywords: Attitude; awareness; community pharmacist; epilepsy; knowledge; PUBLIC AWARENESS; PERCEPTIONS; STUDENTS; RELIABILITY; UNIVERSITY; TEACHERS; VALIDITY; STIGMA; General & Internal Medicine